2013
DOI: 10.1007/s00134-013-3148-9
|View full text |Cite
|
Sign up to set email alerts
|

De-escalation of antimicrobial treatment in neutropenic patients with severe sepsis: results from an observational study

Abstract: Our data suggest that, in ICU, de-escalation of the empirical antimicrobial treatment is frequently applied in neutropenic cancer patients with severe sepsis. No evidence of any prognostic impact of this de-escalation was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 33 publications
6
85
1
7
Order By: Relevance
“…In contrast, de-escalation was associated with an increased use of antimicrobials. This finding was reported in a recent cohort of septic patients with neutropenia [4]. Our study suggests that this was related to an increased number of superinfections in the deescalation group.…”
supporting
confidence: 87%
“…In contrast, de-escalation was associated with an increased use of antimicrobials. This finding was reported in a recent cohort of septic patients with neutropenia [4]. Our study suggests that this was related to an increased number of superinfections in the deescalation group.…”
supporting
confidence: 87%
“…[134][135][136] The first study which enrolled neutropenic patients reported that de-escalation was performed in 44% of patients within the first 12 days after ICU admission. 137 No standardized rules were established for antibiotic switch, leaving to senior doctors the decision to reduce the b-lactam spectrum or to discontinue drugs active against MRSA. This prospective observational analysis did not show any increase in mortality rate at 30 days and at one year after ICU discharge in the de-escalation group.…”
Section: Empirical Therapy In High Risk Patientsmentioning
confidence: 99%
“…The corresponding approach for suspected or documented invasive aspergillosis in ICU patients has also been published [6]. All these data allowed the appraisal of the current epidemiology of infections in immunocompromised patients, and the safe performing of antibiotic de-escalation in patients with neutropenia [7,8]. This strategy, which consists of "de-escalating antimicrobial therapy" by either reducing the number or the spectrum of the molecule used is now part of recently published guidelines [9].…”
Section: Severe Infectionsmentioning
confidence: 99%